Linking Availability Expectations, Bidirectional Boundary Management Behavior and Preferences, and Employee Well-Being: an Integrative Study Approach - Kathrin Reinke; Gisela I. Gerlach (Journal of Business and Psychology, 2021)
Information and communication technologies enable employees to be available anywhere and anytime, raising availability expectations of work and nonwork contacts. Building on the theory of planned behavior and the person-environment fit theory, the present study examines how others' availability expectations predict employees' management of work and nonwork boundaries, and how these bidirectional boundary management behaviors relate to well-being. Results of structural equation modeling with data from 401 employees collected in two waves show that availability expectations of both coworkers and nonwork contacts predict how employees manage the boundaries of work and nonwork domains. Thereby, availability expectations are negatively related to segmentation of the two domains and coworkers' expectations~show an indirect effect on employee well-being. Further, our study shows that work-nonwork and nonwork-work segmentation behavior have divergent effects on employee well-being, indicating that asymmetric boundary management behavior with high work-nonwork segmentation and low nonwork-work segmentation may be beneficial. Besides, moderation analyses underline the importance of enabling individuals to align their boundary management preferences with their actual behavior, especially when individuals have high work-nonwork segmentation preferences. By integrating and unveiling distinct antecedents of work-nonwork and nonwork-work segmentation behavior and their divergent effects on well-being, the present study contributes to a comprehensive framework for investigating and understanding bidirectional boundary management in the face of technology-enabled availability.
Keywords: 650; Information and communication technology (ICT); Availability expectations; Boundary management; Life balance; Employee well-being